2016
DOI: 10.4314/jab.v95i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effet des extraits du thé de Gambie (<i>Lippia multiflora</i> Moldenk) et du neem (<i>Azadirachta indica</i> A. Juss.) sur<i> Helicoverpa armigera</i> et les <i>Thrips</i> de la tomate (<i>Lycopersicon esculentum </i>Mill.)

Abstract: Effet des extraits du thé de Gambie (Lippia multiflora Moldenk) et du neem (Azadirachta indica A. Juss.) sur Helicoverpa armigera et les Thrips de la tomate. 8930 Effet des extraits du thé de Gambie (Lippia multiflora Moldenk) et du neem (Azadirachta indica A. Juss.) sur Helicoverpa armigera et les Thrips de la tomate (Lycopersicon esculentum Mill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…In addition, the soap, which seems to have a biocidal effect, could have reduced the damage due to its larvae. Especially since the work of Traoréet al [22], showed the effectiveness of plant extracts on the tomato moth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the soap, which seems to have a biocidal effect, could have reduced the damage due to its larvae. Especially since the work of Traoréet al [22], showed the effectiveness of plant extracts on the tomato moth.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors pointed out the insecticidal effect of aqueous essences from plants, among them Garba et al (2017) who precised that a 37.5 kg/ha dose of fresh leaves of Azadirachta indica and 10 kg/ha of its seed turned out to be better than reference pesticides. In the same way, according to Traore et al (2015) Ngom (2020) revealed that aqueous essences from fresh leaves of C. procera, by reducing their populations, had significant effect against C. chalcites, H. armigera, H. undalis, P. xylostella, and against winged greenflies living on cabbage farming, too. In Morocco, Abassi et al (2004) pointed out that a primary mixture of alkaloids from C. procera leaves is effective against larvae of fifth stage and against ovarian development of Schistocerca gregaria, and that a death rate of 100% had been reached after 15 days.…”
Section: Effect Of the Different Aqueous Essences On Ravager Insectsmentioning
confidence: 93%
“…R (g/m²) = Mt (g)/S where, R is yield (g/m²); Mtis the total mass of bulbs; S is the surface area (m²). The yield expressed in t/ha was obtained by extrapolation using the yield/m² above (Traore et al, 2015):…”
Section: Assessment Of Growth and Yields Parametersmentioning
confidence: 99%
“…Organic fertilizers such as compost and its extracts, or even plant extracts as biopesticide could be used as alternative, because of advantages they have of being biodegradable, non-persistent in the nature, inexpensive, and more accessible to small producers (Mahmoud et al, 2015). The current trend is the formulation of natural substances such as biopesticides and biofertilizers (Sagoua, 2009;Ekra, 2010;Mouria et al, 2013;Traore et al, 2015;Pale et al, 2021). Previous researches carried out in northern Cameroon have shown the effecacy of compost and their extracts in improving growth and yield as well as reducing the incidence of plant diseases (Ngakou et al, 2008;Anguessin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%